Enhancing Teacher Competence in Developing Local Wisdom-Based Teaching Materials through HyFlex Participatory Workshops in English Teacher Community in Jayapura Regency - Nurul Farida; Yari Dwikurnaningsih; Mawardi (Attractive : Innovative Education Journal, 2026)
The integration of local wisdom in English learning in Jayapura Regency is not optimal due to the gap between teachers' theoretical knowledge and practical skills in developing teaching materials. Factors that influence this are geographical constraints, the lack of written cultural references, and time constraints due to administrative burdens. This study aims to improve teachers' competence in developing teaching materials based on local wisdom through the Hyflex Participatory Workshop. Using the Stringer (Look, Think, Act) School Action Research method in two cycles, the study involved 35 MGMP English teachers in Jayapura Regency as subjects. This study design used a mixed method approach. Data were collected through tests, observations, and documentation, then analyzed using inferential and descriptive statistics. The results showed that active participation of participants increased from 75% in Cycle I to 95% in Cycle II after optimizing hyflex learning (hybrid synchronous, online synchronous, and online asynchronous) with the help of valid and practical LMS and Flipbook guides. Teacher competence increased with an average score rising from 90.7 (pre-test) to 98.4 (post-test) and classical completeness reaching 100%. There was a significant difference in the pre-test and post-test averages based on the Wilcoxon Signed Ranks Test with a Sig. 0.001 (<p=0.05). The action was proven effective in improving teacher competence as evidenced by an N-Gain score of 0.88 (g>0.7). This study resulted in an integrated digital teaching material bank. It was concluded that Hyflex flexibility and participatory collaboration effectively overcome technical and epistemological barriers for teachers in the English MGMP in Jayapura Regency.